Systemic toxicity of thiamethoxam in the mud crab (Scylla paramamosain): Oxidative stress, neurotoxicity, and growth retardation - Zhennan Wang; Ye Sun; Kaiming Luo; Shaolin Yao; Ce Shi; Changkao Mu; Chunlin Wang; Pingping Zhan; Yangfang Ye (Environmental Pollution, 2026)

Asynchronous recovery of hydrolytic and oxidative enzymes during wetland restoration - Xiangling Zhou; Ting Wang; Lifei Su; Siqi Zheng; Shijia Liu; Yi Liu; Wenhui Quan; Tingting Hu; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; et al. (Agriculture, Ecosystems & Environment, 2026)

Cold plasma technology for the modification and quality control of food components via exogenous RONS: Mechanisms, strategies, and future prospects - Xiaotong Fan; Jiabao Ni; Yanxiang Bi; Shiye Luo; Pingping Dong; Shenyuan Quan; Jiaxin He; Xiaoming Fang (Food Bioscience, 2026)

An experiment and application of flood inundation simulation in urban areas - Wei Zhu; Zhe Cao; Kenji Kawaike; Pingping Luo; Kazuki Yamanoi; Takahiro Koshiba (Natural Hazards, 2026)

Electromagnetic-dual-gradient laser-induced graphene/Fe3O4 composites with synergistic gradient-patterning for advanced electromagnetic interference shielding - Pingping Hao; Yajie Hu; Yujie Cao; Boru Du; Mingguang Han; Wei Zhao; Sida Luo (Chemical Engineering Journal, 2026)

Application of a coupled mechanistic and data-driven model for water level prediction considering the temporal and spatial effects of runoff evolution in cascade hydropower stations - Yubin Zhang; Xiaoqun Wang; Jijian Lian; Pingping Luo (Journal of Hydrology, 2026)

A 15,000-year Temperature record from the northern boundary of the east asian summer monsoon based on lacustrine brGDGTs - Nan Zhan; Zeyang Zhu; Pingping Li; Luo Wang; Ruilin Wen; Manman Xie; Qing Sun; Guoqiang Chu (Quaternary Science Reviews, 2026)

Hydrological Effects Assessment of Double-Layer Permeable Pavement by Physical Experimental Basis - Pingping Luo; Yubin Zhang; Shiwen Zhu; Yixuan Zhang; Madhab Rijal; Peiyao Yan; Maochuan Hu (Water Resources Management, 2026)

Integrating machine learning with NSGA-Ⅱ to assess the synchronization effects of stormwater disaster hazard and green–blue infrastructure - Jiaxuan Chen; Sisi Wang; Pingping Luo; Chong-Yu Xu; Hongyu Zhao (Journal of Hydrology, 2026)

A novel integrating quantitative and qualitative approaches for comprehensive assessment of wastewater: combined water quality and community attitudes - Fatima Fida; Pingping Luo; Misbah Fida; Shuangtao Wang; Irshad Hussain; Asim Khan; Liming Liu (Environmental Geochemistry and Health, 2026)

Hydrological response to climate change and urbanization in a semi-arid urban river - Jiqiang Lyu; Yan Wang; Kexin Wang; Wenya Liu; Dongyong Sun; Pingping Luo; Zhaohui Zhou; Meng Jiao; Aidi Huo; Peng Guo (Urban Climate, 2025)

Extreme climate indices in mountain settlements based on a hierarchical urban–rural classification approach in Qinba, China - Kanhua Yu; Wenting Yang; Juan Xu; Pingping Luo; Xuhui Wang; Zhaoyi Li (Urban Climate, 2025)

Hydrolase-oxidase responses mediate distinct carbon dynamics following wetland conversion to paddy versus upland systems - Lifei Su; Yi Liu; Lishan Tan; Xiangling Zhou; Ting Wang; Yinyin She; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; Min Luo (Soil Biology and Biochemistry, 2025)

Retrieving soil heavy metal concentrations using hyperspectral remote sensing images based on three-band indices at a coal mine in China - Haorui Bai; Bin Guo; Lin Pei; Bo Zhang; Pingping Luo; Tengyue Guo; Min Wu; Xiaohan Ma (Advances in Space Research, 2025)

Continuous and freeform manufacturing of hybrid laser-induced graphene and polyimide woven fabrics for enabling smart-textile garments with multifunctional wearable applications - Yajie Hu; Pingping Hao; Boru Du; Yan Gao; Weixiong Yang; Mingguang Han; Zhuang Hao; Haibin Duan; Xilun Ding; Sida Luo (Chemical Engineering Journal, 2025)

Optimizing fertilization enhances sustainable vegetable production: combining on-farm composting and biochar application to improve vegetable yield, soil health, and socio-economic benefits - Bihui Tang; Pingping Ye; Xu Luo; Xinyi Yang; Tao Liang; Anle Chen; Duan Yu; Xiaozhong Wang; Ran Xiao (Journal of Cleaner Production, 2025)

Silk fibroin/collagen hydrogel containing EDIL3 nanoparticles promotes pressure ulcer healing by promoting angiogenesis and remodeling local inflammation - Xuewei Kan; Liwen Luo; Shiyu Zhang; Pingping Yao; Jiaqi Chen; Yuying Jia; Zigang Shen; Zhiqiang Tian; Bing Ni; Jun Tang (Chemical Engineering Journal, 2025)

Risk Assessment of Human and Vehicle Stability in Extreme Weather Events in Coastal Cities - Wei Zhu; Xianbao Zha; Pingping Luo; Shuangtao Wang; Chengyi Xv; Yongxing Ji (Water Resources Management, 2025)

Unexpectedly stable soil organic carbon in tidal marshes under combined nitrogen loading and increased inundation compared to individual effects - Tianning Fan; Jiafang Huang; Guopeng Liang; Shengen Liu; Dehong Hu; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo; Chuan Tong (Limnology and Oceanography, 2025)
Tidal marshes serve as critical carbon (C) sinks, yet face increasing threats from global environmental changes. While previous research has documented how nitrogen (N) loading and sea‐level rise affect total C pools individually, their impacts on soil organic carbon (SOC) stabilization remain critically underexplored, particularly when these factors co‐occur in tidal marsh ecosystems. Through a 3‐yr field experiment, we analyzed how these factors, alone and combined, impact SOC stabilization by examining SOC fraction dynamics. Results showed that N loading increased particulate organic carbon (POC) by 18% and decreased mineral‐associated organic carbon (MAOC) by 13%, reducing SOC stabilization. Conversely, increased inundation raised MAOC by 31% and decreased POC by 19%, promoting SOC stabilization. The decreased MAOC under N loading stemmed from reduced fungal necromass C, while the increased POC related to lower phenol oxidase activity. In contrast, with increased inundation, MAOC rose due to iron‐bound organic C (Fe‐OC) accumulation, while POC declined from increased phenol oxidase activity. When both factors were applied together, SOC stabilization remained at control levels. This occurred because the combined effect maintained oxidative enzyme activities and thus retained POC levels. The simultaneous reduction in fungal necromass C and enhancement of Fe‐OC associations established complementary mechanisms that maintained MAOC at levels equivalent to control. Our findings reveal that N loading and increased inundation drive contrasting patterns of SOC stabilization, while their combination produces uniquely stabilized C dynamics. This insight challenges single‐factor predictions and underscores the importance of multi‐factor experiments in understanding ecosystem responses under concurrent global change scenarios.

Divergence of microbial carbon use efficiency and soil organic carbon along a tidal flooding gradient in a subtropical coastal wetland - Ji Tan; Jiafang Huang; Wenhui Quan; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo (Water Research, 2025)

Dual signal output detection of acetamiprid residues in medicine and food homology products via nanopore biosensor - Yao Li; Jiyuan Tu; Hong Wang; Kexin Luo; Pingping Xiao; Tangbin Liao; Guo-Jun Zhang; Zhongyue Sun (Food Chemistry, 2025)

Temperature variability in northeastern China over the Past 2000 Years: Linkages with the Arctic oscillation and solar activity - Nan Zhan; Fangang Zeng; Qi Li; Manman Xie; Ruixia Hao; Li Pingping; Ruilin Wen; Luo Wang; Qing Sun; Guoqiang Chu (Quaternary International, 2025)

Soil salinity accumulation and groundwater degradation due to overexploitation over recent 40-year period in Yaoba Oasis, China - Ting Lu; Pingping Luo; Jucui Wang; Yudong Lu; Aidi Huo; Liming Liu (Soil and Tillage Research, 2025)

An urban flood inundation model accelerated by the parallel acceleration technology - Wei Zhu; Zhe Cao; Pingping Luo; Shuangtao Wang; Chengyi Xv; Yongxing Ji (Environmental Modelling & Software, 2025)

Treatment of sludge hydrothermal carbonization wastewater by ferrous/sodium percarbonate system: Effect of wastewater composition and role of coagulation and oxidation - Liming Liu; Luna Zhao; Shiyun Jin; Wei Zou; Hongxia Wang; Yu Xie; Changlan Hou; Yunbo Zhai; Pingping Luo (Water Research, 2024)

Real-time predictive control assessment of low-water head hydropower station considering power generation and flood discharge - Yubin Zhang; Xiaoqun Wang; Tianyu Feng; Jijian Lian; Pingping Luo; Madhab Rijal; Wentao Wei (Journal of Hydrology, 2024)

A novel urban flood risk assessment framework based on refined numerical simulation technology - Wei Zhu; Zhe Cao; Kenji Kawaike; Pingping Luo; Kazuki Yamanoi; Takahiro Koshiba (Journal of Hydrology, 2024)

Comparisons of stripe rust response, grain yield and quality between fungicide sprayed and non-sprayed treatments for newly developed wheat lines carrying different genes for adult-plant resistance to stripe rust - Hao Chen; Liangqi Zhang; Chuanguang Ding; Yuqi Luo; Guoyun Jia; Junming Feng; Yuqi Wang; Binfan Si; Jianian Zhou; Xin Li; Kebing Huang; Suizhuang Yang; et al. (Crop Protection, 2024)

A novel quantity assessment of landscape ecological risk using human-nature driving mechanism for sustainable society - Lili Liu; Jiabin Wei; Pingping Luo; Yixuan Zhang; Yihe Wang; Ahmed Elbeltagi; Mohd Remy Rozainy Mohd Arif Zainol (Science of The Total Environment, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Global systematical and comprehensive overview of mountainous flood risk under climate change and human activities - Madhab Rijal; Pingping Luo; Binaya Kumar Mishra; Meimei Zhou; Xiaohui Wang (Science of The Total Environment, 2024)

Atmospheric water demand dominates terrestrial ecosystem productivity in China - You Tu; Xiaofeng Wang; Jitao Zhou; Xiaoxue Wang; Zixu Jia; Jiahao Ma; Wenjie Yao; Xinrong Zhang; Zechong Sun; Pingping Luo; Xiaoming Feng; Bojie Fu (Agricultural and Forest Meteorology, 2024)

Evolution of an arid social-ecosystem with different water utilization spanning 12,000 years - Aidi Huo; Zhixin Zhao; Pingping Luo; Qi Liu; Qiangbing Huang; Zhenhong Wang; Jianbing Peng (Journal of Cleaner Production, 2024)

Optimizing the deployment of LID facilities on a campus-scale and assessing the benefits of comprehensive control in Sponge City - Xianbao Zha; Wei Fang; Wei Zhu; Shuangtao Wang; Yong Mu; Xiaofeng Wang; Pingping Luo; Mohd Remy Rozainy Mohd Arif Zainol; Mohd Hafiz Zawawi; Khai Lin Chong; Apip Apip (Journal of Hydrology, 2024)

Analyte-perturbed balance between reducibility and fluorescence of Ti3C2 MXene quantum dots for label-free, dual-mode detection of silver ions - Peng Jin; Pingping Wan; Chunyan Zhang; Xu Li; Yan Wang; Jianxin Luo; Kun Li (Analytica Chimica Acta, 2024)

NtERF4 promotes the biosynthesis of chlorogenic acid and flavonoids by targeting PAL genes in Nicotiana tabacum - Shun He; Xin Xu; Qian Gao; Changjun Huang; Zhaopeng Luo; Pingping Liu; Mingzhu Wu; Haitao Huang; Jun Yang; Jianmin Zeng; Zhong Wang (Planta, 2024)

Historical and comparative overview of sponge campus construction and future challenges - Pingping Luo; Peiyao Yan; Xiaohui Wang; Yang Wu; Jiqiang Lyu; Bin He; Weili Duan; Shuangtao Wang; Xianbao Zha (Science of The Total Environment, 2024)

Increase in iron-bound organic carbon content under simulated sea-level rise: A “marsh organ” field experiment - Dehong Hu; Wenjing Lan; Min Luo; Tianning Fan; Xin Chen; Ji Tan; Shihua Li; Pingping Guo; Jiafang Huang (Soil Biology and Biochemistry, 2023)

Rasterizing CO2 emissions and characterizing their trends via an enhanced population-light index at multiple scales in China during 2013–2019 - Bin Guo; Tingting Xie; Wencai Zhang; Haojie Wu; Dingming Zhang; Xiaowei Zhu; Xuying Ma; Min Wu; Pingping Luo (Science of The Total Environment, 2023)

Spatiotemporal characteristics and influencing factors of carbon emissions from land-use change in Shaanxi Province, China - Wei Fang; Pingping Luo; Lintao Luo; Xianbao Zha; Daniel Nover (Environmental Science and Pollution Research, 2023)

Quantitative assessment of spatiotemporal dynamics in vegetation NPP, NEP and carbon sink capacity in the Weihe River Basin from 2001 to 2020 - Jiqiang Lyu; Xianghang Fu; Chen Lu; Yueyan Zhang; Pingping Luo; Peng Guo; Aidi Huo; Meimei Zhou (Journal of Cleaner Production, 2023)

Experimental study on slope morphological characteristics and stability analysis of GCHP engineering in the loess plateau - Zhixin Zhao; Aidi Huo; Yuxiang Cheng; Pingping Luo; Jianbing Peng; Ahmed Elbeltagi; Mohamed EL-Sayed Abuarab; Ali Mokhtar (Advances in Space Research, 2023)

Incorporation of ascorbic acid and L-cysteine in sodium carboxymethyl cellulose coating delays color deterioration and extends the shelf-life of fresh-cut asparagus lettuce (Lactuca sativa var. angustata) - Renying Yu; Huibo Song; Yanan Chen; Nan Shi; Hui Shen; Pingping Shi; Huosheng Shu; Xiaoxue Kong; Lijuan Yu; Haibo Luo (Postharvest Biology and Technology, 2023)

Incorporating biotic phosphorus-acquisition strategies into soil phosphorus transformation under long-term salinization in a tidal wetland - Tianning Fan; Min Luo; Ji Tan; Dehong Hu; Xin Chen; Jiafang Huang; Shihua Li; Pingping Guo; Ji Chen (CATENA, 2023)

The transcription factor NtERF13a enhances abiotic stress tolerance and phenylpropanoid compounds biosynthesis in tobacco - Zhong Wang; Jinchu Yang; Qian Gao; Shun He; Yongming Xu; Zhaopeng Luo; Pingping Liu; Mingzhu Wu; Xin Xu; Lanxin Ma; Zhan Zhang; Yongfeng Yang; et al. (Plant Science, 2023)

Enhancing adsorption capacity and herbicidal efficacy of 2,4-D through supramolecular self-assembly: Insights from cocrystal engineering to solution chemistry - Yuntian Xiao; Chuanhua Wu; Pingping Cui; Xiaofang Luo; Ling Zhou; Qiuxiang Yin (Chemical Engineering Journal, 2023)

A novel design and application of spatial data management platform for natural resources - Weijiang Kong; Tengji Wang; Lili Liu; Pingping Luo; Jianjun Cui; Ligang Wang; Xiankang Hua; Weili Duan; Feng Su (Journal of Cleaner Production, 2023)

HADHA alleviates hepatic steatosis and oxidative stress in NAFLD via inactivation of the MKK3/MAPK pathway - Jiexia Ding; Lili Wu; Guoxian Zhu; Jing Zhu; Pingping Luo; Youming Li (Molecular Biology Reports, 2023)
Background Nonalcoholic fatty liver disease (NAFLD) is a liver metabolic syndrome and still lacks effective treatments because the molecular mechanism underlying the development of NAFLD is not completely understood. We investigated the role of Hydroxyl CoA dehydrogenase alpha subunit (HADHA) in the pathogenesis of NAFLD. Methods HADHA expression was detected both in NAFLD cell and mice, and knockdown of HADHA in free fatty acids (FFA)-treated L02 or overexpression of HADHA in high fat diet (HFD)-fed mice was used to detected the influence of HADHA on hepatic steatosis, mitochondrial dysfunction, and oxidative stress by regulating of MKK3/MAPK signaling. Results Our data revealed that HADHA expression was decreased in FFA-treated L02 cells and in HFD-fed mice. Knockdown of HADHA markedly aggravated hepatic steatosis, inflammation and oxidative stress in FFA-treated L02 cells, which was associated with the activation of MKK3/MAPK signalling pathways. Moreover, oxidative stress and liver lesions were improved in NAFLD mice by upregulation of HADHA. Importantly, we demonstrated that overexpression of HADHA inhibited the expression of p-MAPK in NAFLD mice, reducing lipid accumulation and steatosis. Conclusion HADHA may function as a protective factor in the progression of NAFLD by alleviating abnormal metabolism and oxidative stress by suppressing MKK3/MAPK signalling pathway activation, providing a new target for the treatment of NAFLD.

Transcription factor NtWRKY33a modulates the biosynthesis of polyphenols by targeting NtMYB4 and NtHCT genes in tobacco - Zhong Wang; Lanxin Ma; Pingping Liu; Zhaopeng Luo; Zefeng Li; Mingzhu Wu; Xin Xu; Wenxuan Pu; Pingjun Huang; Jun Yang (Plant Science, 2023)

A quantitative analysis of research trends in flood hazard assessment - Wei Zhu; Xianbao Zha; Pingping Luo; Shuangtao Wang; Zhe Cao; Jiqiang Lyu; Meimei Zhou; Bin He; Daniel Nover (Stochastic Environmental Research and Risk Assessment, 2023)

Exploring sustainable solutions for the water environment in Chinese and Southeast Asian cities - Pingping Luo; Yong Mu; Shuangtao Wang; Wei Zhu; Binaya Kumar Mishra; Aidi Huo; Meimei Zhou; Jiqiang Lyu; Maochuan Hu; Weili Duan; Bin He; Daniel Nover (Ambio, 2022)

Glutamate and aspartate alleviate testicular/epididymal oxidative stress by supporting antioxidant enzymes and immune defense systems in boars - Wenjie Tang; Jian Wu; Shunshun Jin; Liuqin He; Qinlu Lin; Feijun Luo; Xingguo He; Yanzhong Feng; Binsheng He; Pingping Bing; Tiejun Li; Yulong Yin (Science China Life Sciences, 2020)

Applying a water quality index model to assess the water quality of the major rivers in the Kathmandu Valley, Nepal - Ram Krishna Regmi; Binaya Kumar Mishra; Yoshifumi Masago; Pingping Luo; Asako Toyozumi-Kojima; Shokhrukh-Mirzo Jalilov (Environmental Monitoring and Assessment, 2017)

Spatiotemporal variability of Hokkaido's seasonal precipitation in recent decades and connection to water vapour flux - Weili Duan; Bin He; Netrananda Sahu; Pingping Luo; Daniel Nover; Maochuan Hu; Kaoru Takara (International Journal of Climatology, 2017)
Based on 169 stations, annual, seasonal and monthly precipitation trends for the northern Japanese island of Hokkaido were analysed for the period 1980–2011 using the Mann–Kendall test and geostatistical interpolation techniques. Possible association with water vapour flux was explored using ERA ‐Interim reanalysis data. Precipitation increased in Hokkaido over the study period at both the annual and seasonal scales. In general, the northwest had higher precipitation than the southeast in winter, autumn and on an interannual basis and precipitation tended to be concentrated in the southeast in both spring and summer. There was also more precipitation during warm times of the year. For example, precipitation occurred mainly during the summer, ranging from 233 to 751 mm and autumn, ranging from 218 to 724 mm, while precipitation was significantly less in winter and spring. Most stations with declining precipitation trends were located in areas with higher precipitation, such as the west in winter and autumn and the southeast fringe in summer and scattered across the areas with lower precipitation in spring. Increases in precipitation were mainly seen in February, May, June, July, September, November and December at more than 100 stations. Amongst these, almost all of the stations showed positive trends in May (168 stations) and July (165 stations). Finally, the changes of the water vapour transport and budget in whole‐layers between the period 1980–2011 possibly explained the spatiotemporal distribution of precipitation trends in Hokkaido.

Assessment of hydrological extremes in the Kamo River Basin, Japan - Maochuan Hu; Takahiro Sayama; Weili Duan; Kaoru Takara; Bin He; Pingping Luo (Hydrological Sciences Journal, 2017)

Chasing ghosts: allopolyploid origin of Oxyria sinensis (Polygonaceae) from its only diploid congener and an unknown ancestor - Xin Luo; Quanjun Hu; Pingping Zhou; Dan Zhang; Qian Wang; Richard J. Abbott; Jianquan Liu (Molecular Ecology, 2017)
Reconstructing the origin of a polyploid species is particularly challenging when an ancestor has become extinct. Under such circumstances, the extinct donor of a genome found in the polyploid may be treated as a ‘ghost’ species in that its prior existence is recognized through the presence of its genome in the polyploid. In this study, we aimed to determine the polyploid origin of Oxyria sinensis (2 n = 40) for which only one congeneric species is known, that is diploid O. digyna (2 n = 14). Genomic in situ hybridization (GISH), transcriptome, phylogenetic and demographic analyses, and ecological niche modelling were conducted for this purpose. GISH revealed that O. sinensis comprised 14 chromosomes from O. digyna and 26 chromosomes from an unknown ancestor. Transcriptome analysis indicated that following divergence from O. digyna , involving genome duplication around 12 million years ago (Ma), a second genome duplication occurred approximately 6 Ma to give rise to O. sinensis . Oxyria sinensis was shown to contain homologous gene sequences divergent from those present in O. digyna in addition to a set that clustered with those in O. digyna . Coalescent simulations indicated that O. sinensis expanded its distribution approximately 6–7 Ma, possibly following the second polyploidization event, whereas O. digyna expanded its range much later. It was also indicated that the distributions of both species contracted and re‐expanded during the Pleistocene climatic oscillations. Ecological niche modelling similarly suggested that both species experienced changes in their distributional ranges in response to Quaternary climatic changes. The extinction of the unknown ‘ghost’ tetraploid species implicated in the origin of O. sinensis could have resulted from superior adaptation of O. sinensis to repeated climatic changes in the region where it now occurs.

Changes of precipitation amounts and extremes over Japan between 1901 and 2012 and their connection to climate indices - Weili Duan; Bin He; Kaoru Takara; Pingping Luo; Maochuan Hu; Nor Eliza Alias; Daniel Nover (Climate Dynamics, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

PI3K/Akt/uncoupling protein 2 signaling pathway may be involved in cell senescence and apoptosis induced by angiotensin II in human vascular endothelial cells - Ping Li; Xin Guo; Pingping Lei; Shoujun Shi; Shike Luo; Xiaoshu Cheng (Molecular Biology Reports, 2014)

Anomalous atmospheric events leading to Kyushu’s flash floods, July 11–14, 2012 - Weili Duan; Bin He; Kaoru Takara; Pingping Luo; Daniel Nover; Yosuke Yamashiki; Wenrui Huang (Natural Hazards, 2014)

Endogenous enkephalin does not contribute to the cerebral anti-hyperalgesic action of gabapentin - ShaoHui Chen; Jing Zhao; YuGuang Huang; AiLun Luo; PingPing Zuo; Nan Yang; WenYu Hao (Science China Life Sciences, 2010)